1996
DOI: 10.1271/bbb.60.330
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Strain ofBacillus megateriumThat Degrades Poly(vinyl alcohol)

Abstract: A poly(vinyl alcohol) (PVA)-degrading mixed culture that consisted of sereval microorganisms was obtained from activated sludge from a textile factory. From the culture, a component bacterial strain, BX1, that degraded PVA was isolated, and was identified as Bacillus megaterium. This strain could degrade PVA only in the cocultivation with a bacterial strain, PN19, that was isolated from the same mixed culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 3 publications
0
45
0
Order By: Relevance
“…Phylogenetic and physiological analyses reveal that strains iso- (48)(49)(50)(51)(52)(53). In light of the diversity of Bacillus strains able to grow under scCO 2 , we hypothesize that the ability to grow under high pCO 2 is a widespread feature of Bacillus spp.…”
Section: Discussionmentioning
confidence: 94%
“…Phylogenetic and physiological analyses reveal that strains iso- (48)(49)(50)(51)(52)(53). In light of the diversity of Bacillus strains able to grow under scCO 2 , we hypothesize that the ability to grow under high pCO 2 is a widespread feature of Bacillus spp.…”
Section: Discussionmentioning
confidence: 94%
“…There were different species of bacteria and fungi according to the type of buried membrane and the concentration of the polymer. The buried chromated pure PVA membrane, the dominant species were Bacillus spp [25,45,46,47,48,49], Pseudomonas spp [27,31,50,47,48], Aspergillus spp [51] and Penicillium spp [27,47]. In addition, for the buried GA, the major species were Bacillus spp [6,12,45], Penicillium spp, Aspergillus spp, Rhizorpous spp, [6,33,34].…”
Section: Biodegradation Bacteria and Fungimentioning
confidence: 99%
“…This results agree with Coleman and Paran [52] who concluded that Gram-negative chromium reducing-bacteria tend to be more sensitive to chromium ion, while Gram positive bacteria are significantly tolerant to chromate ion toxicity even at relatively high concentration of the ion [25,52]. Moreover, the microbial communities of the bioplastic blends, namely (chromated GA/PVA=1:1), (chromated GA/PVA=1:0.75), (chromated GA/PVA=0.5) and (GA/PVA=1:0.25) contained Bacillus spp [25,45,46,49,53], Pseudomonas spp [27,31,47,48,50], Aspergillus spp, Rhizorpous spp, and Penicillium spp. [33].…”
Section: Biodegradation Bacteria and Fungimentioning
confidence: 99%
“…Polyvinyl alcohol (PVA) with its carbon-carbon backbone, being water soluble can be biodegraded under both aerobic and anaerobic conditions (Suzuki et al 1973;Watanabe et al 1976;Sakazawa et al 1981;Shimao et al 1983;Mori et al 1996;Matsumura et al 1993) and therefore finds application in the manufacture of carriers used in delivery system for chemicals such as fertilizer, pesticides (Premraj and Doble 2005), in the textile, papercoating and chemical industries (Qian et al 2004) and also as the biodegradable backbone in sugar and fatty acidbranched polymers (Tokiwa et al 2000). The annual world production of PVA is about 0.65 million tons/year, and a large amount of the used and discarded PVA also poses a significant waste problem (Tokiwa et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They include Pseudomonas O-3 (Suzuki et al 1973), Pseudomonas sp. (Shimao et al 1984(Shimao et al , 1986(Shimao et al , 1996Watanabe et al 1975Watanabe et al , 1976Sakai et al 1981Sakai et al , 1985a, Alcaligenes faecalis (Matsumura et al 1993) and Bacillus megaterium (Mori et al 1996). Among fungi, Penicillium sp.…”
Section: Introductionmentioning
confidence: 99%